2008
DOI: 10.1016/j.tourman.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of SARS and Avian Flu on international tourism demand to Asia

Abstract: The purpose of this paper is to investigate the impacts of infectious diseases including Avian Flu and severe acute respiratory syndrome (hereafter SARS) on international tourist arrivals in Asian countries using both single datasets and panel data procedures. An autoregressive moving average model together with an exogenous variables (ARMAX) model are used to estimate the effects of these diseases in each SARS- and Avian Flu-infected country, while a dynamic panel model is adopted to estimate the overall impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(300 citation statements)
references
References 24 publications
6
261
0
9
Order By: Relevance
“…Because of different levels of damage, the tourism industry in Asian countries was affected to different degrees by SARS (Page et al 2006;Kuo et al 2008). China was affected most; not only was tourism impacted but also retail sales, restaurants, hotels and the air transport industry (Keogh-Brown, Richard 2008).…”
Section: S113mentioning
confidence: 99%
“…Because of different levels of damage, the tourism industry in Asian countries was affected to different degrees by SARS (Page et al 2006;Kuo et al 2008). China was affected most; not only was tourism impacted but also retail sales, restaurants, hotels and the air transport industry (Keogh-Brown, Richard 2008).…”
Section: S113mentioning
confidence: 99%
“…Song & Li (2008) and Song et al (2012) in their survey of literature related to tourism demand studies have concluded that tourist arrival is the leading measurement in measuring tourism demand followed by other measurements such as tourism receipts and length of stay. Some examples of studies that measured tourism demand in terms of tourist arrivals include those of Dritsakis & Gialitaki (2001), Garin-Munoz (2006), Kuo, Chen, Tseng, Ju, & Huang (2008), Mohd Hanafiah, Mohd Harun, & Jamaluddin (2010), Kusni, Kadir, & Nayan (2013), and Puah, Thien, & Arip (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that disasters impact tourism destinations [2,4,[48][49][50][51]. Disasters make tourism destinations vulnerable, and especially vulnerable when the community manages the tourism destination in a 'communal' way, namely as an informal organization that depends strongly on social commitment.…”
Section: Discussionmentioning
confidence: 99%